Role of Intrapartum Cardiotocography to Predict the Fetal Outcome in High-Risk Patients : A Prospective Study (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2026)
Background: Labour is a very short period of life of a fetus but poses physiological stress to all the fetus. Fetal distress is a progressive condition that, if not corrected, can increase the chance of fetal death. So routine and continuous monitoring of fetal heart rate by doing Cardiotocography in labour in high risk pregnancies has become an established obstetric practice. The aim of the study is to evaluate the predictive value of the admission CTG in detecting fetal hypoxia at the time of admission during labour and to correlate its result with fetal outcome in high risk pregnancies. Materials and methods: This prospective observational study was held in ChattogramMaa O Shishu Hospital Medical College from March 2022 to August 2022. A total of 65 gravid women with high risk pregnancies of >37 weeks gestation with cephalic presentation in the first stage of labour were taken. Result was assessed in the form of APGAR SCORE at 5 min, NICU admission, perinatal mortality and mode of delivery. Statistical analysis was done by using SPSS 20. Chi square test was used and p< 0.05 is considered statistically significant. Results: A total of 65 high risk obstetric patients were recruited. The admission CTG were reactive in 45 patients (69.23%) and non-reactive in 20 patients (30.77%). APGAR SCORE